1987
DOI: 10.1016/0092-8674(87)90619-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein import: Nucleoside triphosphates are involved in conferring import-competence to precursors

Abstract: The role of nucleoside triphosphates (NTPs) in mitochondrial protein import was investigated with the precursors of N. crassa ADPlATP carrier, F1-ATPase subunit 9, F,-ATPase subunit 9, and fusion proteins between subunit 9 and mouse dihydrofolate reductase. NTPs were necessary for the initial interaction of precursors with the mitochondria and for the completion of translocation of precursors from the mitochondrial surface into the mitochondria. Higher levels of NTPs were required for the latter reactions as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
220
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 319 publications
(224 citation statements)
references
References 63 publications
4
220
0
Order By: Relevance
“…However, when the dissipation of A^is combined with a lowering of the temperature (to 2°C) or of the levels of ATP, the precursor remains on the surface of the mitochondria accessible to externally added proteases. Raising the temperature or the levels of ATP leads to insertion of the precursor into the second binding sites described above (3,8). These studies show the existence of two subsequent binding sites on the import pathway of ADP/ATP carrier.…”
Section: Import Intermediates At the Level Of Specific Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the dissipation of A^is combined with a lowering of the temperature (to 2°C) or of the levels of ATP, the precursor remains on the surface of the mitochondria accessible to externally added proteases. Raising the temperature or the levels of ATP leads to insertion of the precursor into the second binding sites described above (3,8). These studies show the existence of two subsequent binding sites on the import pathway of ADP/ATP carrier.…”
Section: Import Intermediates At the Level Of Specific Bindingmentioning
confidence: 99%
“…Major portions of the precursors, however, were still outside the outer membrane as they were accessible to proteases or to antibodies added to isolated mitochondria. Thus, the precursor proteins were reaching from the outside of the outer membrane into the matrix thereby spanning sites of close contact between both membranes (translocation contact sites) (3,8,(10)(11)(12). The translocation intermediates with bound antibodies were decorated with protein-A-gold particles.…”
Section: Import Intermediates In Translocation Contact Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that an enzymatic unfolding activity is necessary for the denaturation of native proteins that are to be translocated across microsomal [11,12] and mitochondrial [11,19] membranes. This activity has been attributed to a member(s) of the 70 kDa heat shock protein family (hsp 70).…”
Section: Resultsmentioning
confidence: 99%
“…Various methods were developed for the accumulation of precursor proteins in mitochondrial contact sites: import of precursor proteins at low temperature [9,15,20]; lowering the levels of ATP in the import reaction [21]; prebinding of specific antibodies to portions of the precursor proteins [9,20]; and, induction of a stable tertiary structure in a domain of a precursor protein [18,19,22]. The underlying principle of these methods is that a (usually carboxyl-terminal) portion of a precursor protein is either not or only partially unfolded and thus cannot be inserted into the mitochondrial membranes.…”
Section: Role Of Contact Sites In Import Of Precursor Proteinsmentioning
confidence: 99%